2015
DOI: 10.1111/ced.12686
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors of childhood acne in Korea: a cross-sectional community based study

Abstract: In the current study, the prevalence of acne among elementary schoolchildren was high, but only a few children had received treatment. Physicians should be attentive to childhood acne, and educate patients and their parents about the need to treat it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 24 publications
4
37
1
2
Order By: Relevance
“…Therefore, pre‐adolescent acne without underlying endocrinopathy is now considered a normal variant of acne . In our study, we reported a prevalence of acne of 34.3% in patients aged from 9–14 years, a percentage which is very similar to the one reported in Korean children (36.2%) but higher than in Taiwan (17.5%) . Furthermore, our findings confirmed that acne prevalence tends to increase with age as reported by previous studies .…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, pre‐adolescent acne without underlying endocrinopathy is now considered a normal variant of acne . In our study, we reported a prevalence of acne of 34.3% in patients aged from 9–14 years, a percentage which is very similar to the one reported in Korean children (36.2%) but higher than in Taiwan (17.5%) . Furthermore, our findings confirmed that acne prevalence tends to increase with age as reported by previous studies .…”
Section: Discussionsupporting
confidence: 90%
“…Finally, four cohort studies, 7-9,22 5 case-control, [10][11][12][13]23 and four cross-sectional studies [24][25][26][27] were included into our meta-analysis. The remaining 181 articles were screened for titles and abstracts and 26 articles were considered of interest and full texts were assessed for further evaluation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Current research suggests that the occurrence of acne is primarily related to factors such as skin surface lipid (SSL) alterations, hormone levels, bacterial infection and inflammatory reactions . Acne can also be related to blood lipids, diet and levels of obesity . In addition to other factors, quantitative and qualitative modifications in SSL are believed to be among the most critical factors in the pathogenesis of acne .…”
mentioning
confidence: 99%